(untitled) (Research, Society and Development, 2021)
Introduction: Venous thromboembolism is a complication that occurs in plastic surgery and can be potentially serious. Objective: to review studies and evidence related to prevention protocols for venous thromboembolism in the field of plastic surgery. Methodology: descriptive research of the integrative literature review type, carried out in July 2021, through online access in the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (Scielo), Cochrane Database of Systematic Reviews (CDSR), Google Scholar, Virtual Health Library (VHL) and EBSCO Information Services. Results: From the comprehensive review of the literature, it is observed that there are controversies between studies, that is, there is still no consensus among authors regarding prophylaxis for venous thromboembolism in plastic surgery. Some authors reiterate that healthy patients with no history of comorbidities do not need to start prophylaxis for VTE. However, there are scholars who emphasize the significant risk of developing a VTE in plastic surgery, especially in surgical procedures that present determinants such as operating time above 2 hours, type of decubitus and procedure, in addition to combined surgeries. In this sense, there are studies that support the use of chemoprophylactics, such as enoxaparin and rivaroxaban, according to the uniqueness of the individual and the procedure, aiming, above all, to preserve the patient’s health. Conclusion: Based on these findings, thromboprophylaxis is the best prevention strategy in surgical patients, considering that each case is unique, and the risk of venous thromboembolism depends both on the patient’s condition and on the procedure performed.